American Vikings : how the Norse sailed into the lands and imaginations of America - Whittock, Martyn, 1958- (Pegasus Books, 2023)
"Vikings are an enduring subject of fascination. The combination of adventure, mythology, violence, and exploration continues to grip our attention. As a result, for more than a millennium the Vikings have traveled far and wide, not least across the turbulent seas of our minds and imaginations. The geographical reach of the Norse was extraordinary. For centuries medieval sagas, first recorded in Iceland, claimed that Vikings reached North America around the year 1000. This book explores that claim, separating fact from fiction and myth from mischief, to assess the enduring legacy of this claim in America. The search for "American Vikings" connects a vast range of different areas; from the latest archaeological evidence for their actual settlement in North America to the myth-making of nineteenth-century Scandinavian pioneers in the Midwest; and from ancient adventurers to the political ideologies in the twenty-first century. It is a journey from the high seas of a millennium ago to the swirling waters and dark undercurrents of the online world of today. No doubt, the warlike Vikings would have understood how their image could be "weaponized." In the same way, they would probably have grasped how their dramatic, violent, passionate, and discordant mythologies could appeal to our era and cultural setting. They might, though, have been more surprised at how their image has been commercialized and commodified. A vivid new history by a master of the form, American Vikings explores how the Norse first sailed into the lands, and then into the imaginations, of America" --